Distal Humeral Diaphyseal Open Fracture in a Child with Bone Loss - Shrestha, Sabin; Shrestha, Dinesh Kumar (Journal of Nepalgunj Medical College, 2021)
Distal diaphyseal humerus fracture is less common than supracondylar humeral fracture and its open fracture is even less. This is a case report of open distal humeral diaphyseal fracture on the left arm with bone loss in 10 years old male who sustained the injury from fall, diagnosed as Grade III open unstable distal diaphyseal shaft fracture of left humerus with bone loss without neurovascular deficit. We performed Open Reduction /Internal Fixation (OR/IF) and free bone fragment was flipped and fixed to the bone fragments and maximum possible contact was made and fixed with an external fixator. Range of motion was advised as early as possible. At final follow up the result was excellent as per Flynn's criteria. OR/IF (Open Reduction /Internal Fixation) of this fracture with posterior approach and flipping the bone to get more contact seems good and safe procedure. Further, external fixation provides reasonable fixation in these cases.